2020
DOI: 10.1002/art.41213
|View full text |Cite
|
Sign up to set email alerts
|

Role of Low‐Density Lipoprotein in Early Vascular Aging Associated With Systemic Lupus Erythematosus

Abstract: Objective. Patients with systemic lupus erythematosus (SLE) often have atherosclerotic complications at a young age but normal low-density lipoprotein (LDL) levels. This study was undertaken to investigate the role of LDL composition in promoting early vascular aging in SLE patients.Methods. Plasma LDL from 45 SLE patients (SLE-LDL) and from 37 normal healthy controls (N-LDL) was chromatographically divided into 5 subfractions (L1-L5), and the subfraction composition was analyzed. Correlations between subfract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…With a multistep linear gradient of buffer B (1 M NaCl in buffer A) at a flow rate of 2 mL/min under observation at 280 nm, the LDL-χ and VLDL-χ subfractions were eluted, separately concentrated by using Centriprep filters (YM-30; EMD Millipore Corp., Billerica, MA) and sterilized by being passed through 0.22-μm filters. The protein concentration of the LDL and VLDL samples was measured by using the Lowry method [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…With a multistep linear gradient of buffer B (1 M NaCl in buffer A) at a flow rate of 2 mL/min under observation at 280 nm, the LDL-χ and VLDL-χ subfractions were eluted, separately concentrated by using Centriprep filters (YM-30; EMD Millipore Corp., Billerica, MA) and sterilized by being passed through 0.22-μm filters. The protein concentration of the LDL and VLDL samples was measured by using the Lowry method [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…L5 also upregulates the expression of IL-6 and IL-8 on both monocytes and macrophages. We have previously shown that L5 induces the expression of lectin-like oxidized LDL receptor-1 (LOX-1) [15], a receptor that is involved in a variety of atherogenic responses including foam cell formation [16]. The combination of foam cell accumulation and increased cytokine activity in the microenvironment synergistically promotes plaque formation (Figure 4).…”
Section: Proposed Model For the Potential Role Of L5 In Ra-related Atmentioning
confidence: 99%
“…Increasing evidence indicates a vital role for L5 in the pathogenesis of atherosclerosis [14]. We recently reported that an elevated the percentage of L5 in LDL (L5%) is associated with an increased CVD risk in patients with RA or systemic lupus erythematosus [15,16]. Therefore, it is important to study the role of L5 in foam cell formation in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…With a multistep linear gradient of buffer B (1 M NaCl in buffer A) at a ow rate of 2 mL/min under observation at 280 nm, the LDL-χ and VLDL-χ subfractions were eluted, separately concentrated by using Centriprep lters (YM-30; EMD Millipore Corp., Billerica, MA) and sterilized by being passed through 0.22-μm lters. The protein concentration of the LDL and VLDL samples was measured by using the Lowry method [31,32].…”
Section: Laboratory Testing For Biochemical Indicators and The Quantimentioning
confidence: 99%